Posttranslational Arginylation Enzyme Arginyltransferase1 Shows Genetic Interactions With Specific Cellular Pathways in vivo - Wiley, David J.; D’Urso, Gennaro; Zhang, Fangliang (Frontiers in Physiology, 2020)
Arginyltransferase1 (ATE1) is a conserved enzyme in eukaryotes mediating posttranslational arginylation, the addition of an extra arginine to an existing protein. In mammals, the ate1 gene is shown to be essential for the development and maintenance of the cardiovascular system. Although biochemical evidence suggested that arginylation may be involved in protein degradation or stress response, the physiological role of ATE1 in vivo remains poorly defined, which leads to difficulties for interpreting its role in diseases pathogenesis. In this study, we take advantage of the Schizosaccharomyces pombe (S. pombe) knockout library to investigate the genetic interactions between ate1 and other genes. By this systematic and unbiased approach, we found that less than 5% of the 3659 tested genes displayed significant genetic interactions with ate1. Furthermore, these genes can be grouped into a few discrete clustered categories based on their functions or their physical interactions. Major functional categories of the ate1-interacting genes include translation/transcription regulation, biosynthesis of biomolecules (including histidine), cell morphology and cellular dynamics, response to oxidative stress and metabolic stress, ribosomal structure and function, and mitochondrial function. Surprisingly, inconsistent to popular belief, very few genes in the global ubiquitination or degradation pathway showed interactions with ate1. The small and focused gene interaction network of ate1 suggest that it specifically regulates a handful of cellular processes in vivo.